Gargalos e demandas da infraestrutura portuária e os investimentos do PAC: Mapeamento IPEA de obras portuárias - Carlos Alvares da Silva Campos Neto; Bolívar Pêgo Filho; Alfredo Eric Romminger; Ians\~a Melo Ferreira; Leonardo Fernandes S. Vasconcelos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The present work discusses the main economical and institutional problems that involve Brazilian ports. Firstly, we characterize the Brazilian ports` segment, presenting the main concepts and the current model. Next, we present a short analysis of the main laws which regulate the sector. Then, we describe the financing model for this segment - public as well as private. Afterwards, we present the major infra-structural demands, consolidating the Mapeamento Ipea de Obras Portuárias, followed by an analysis of how has the government program, PAC, been impacting over those needs. Yet, we state the results of a research made by Ipea about the difficulties potential clients find on using Brazilian ports. And finally, we describe the general results of our analysis.
Keywords: F10; H41; R40; 330